(untitled) (Research, Society and Development, 2020)
Objective: To report the experience, from the perspective of a fellow, about the development of extension actions in a project of comprehensive care to LGBT health. Method: This is an experience report that took place between March 2018 and March 2020 on the development of the extension actions of the project “Comprehensive health care for LGBT people - building nursing care spaces for transsexuals” held at a university in the municipality of Rio de Janeiro. Results: The impact of the scholarship holder is highlighted when performing an analysis of the data obtained in the first contact with the transsexual person who was admitted to perform the surgery, and showing that the various situations that were negatively experienced by the transsexual are incompatible with the various indicators and markers , often expressed in literature, pointing to an illusory functionality of public policies and actions. Conclusion: The extension project fulfilled its role insofar as it enabled the theory-practice relationship to take effect, linked to the critical analysis of the socio-political context of the time, and in the establishment of actions that fill the knowledge and research gaps.